Implementation of Small Sided Game in Improving Aerobic Capacity of Futsal Women Players at STKIP Muhammadiyah Kuningan - Ribut Wahidi; Intan Aprilia Utami; Oman Hadiana; Firman Adityatama (Universitas Majalengka, 2021)
The purpose of this study was to determine the effect of small sided game training on aerobic capacity in futsal. This research method is an experimental method with a one-group pretest-posttest design research. The sample used is 12 futsal players in the Women's Futsal UKM STKIP Muhammadiyah Kuningan. The instrument used in this study was the bleep test. Data analysis techniques in this study using prerequisite test analysis and hypothesis testing. The results obtained by researchers from the results of the calculation of the T test paired sample test explained that there is a significant difference in the effect of the aerobic capacity level using the small sided game method.